How Traders Market Their Trade at The “Lok Baintan” Floating Market, Banjar Regency - Sabhan Sabhan; Moh. Fatah Yasin; Noor Cahaya; Faradina Faradina; Arum Murdianingsih (Social Studies Conference Proceedings, 2022)
This study aims to describe how traders market their wares at the Lok Baintan Floating Market, Banjar Regency. The method used is the observation method. The research data source is the words and actions of traders in the traditional market. Research data in the form of words, sentences, attitudes, and actions of traders. Data analysis is done by identifying, classifying, interpreting, and verifying. The results showed that traders carried out marketing on the river with boats used to approach visitors to offer their wares. Many traders offer their wares, namely in six ways, namely (1) lifting, (2) thrusting, (3) handing it to visitors, and (4) asking for tasting (fruit/food), (5) pantun, and 6) government assistance.